The Importance of Design Storm Hyetograph on Urban Flood Risk Management and Drainage System Design - Egle Saaremäe; Ottar Tamm; Harri Koivusalo; Toomas Tamm (Journal of Flood Risk Management, 2025)
ABSTRACT There is an urgent need to assess the uncertainties in stormwater pipe design owing to the increasing occurrence of urban floods triggered by urbanisation and climate change. The design storm concept involves determining the event duration and corresponding depth. Various design hyetograph methods are available to partition the design storm depth into segments, which raises questions about their impact on stormwater system design. This study analysed an ensemble of eight widely used hyetograph methods, including triangular, linear/exponential, Chicago and alternating block, in industrial and residential urban catchments using the stormwater management model. The modelling results revealed clear disparities between hyetograph methods in terms of catchment hydrological response. Depending on the method used, the simulated outlet peak flow varied by ±30% in both catchments. As a result, outlet pipe sizes varied by one and two increments in the residential and industrial catchments, respectively. Almost no flooding was evident in the manholes using simple single‐point hyetographs, whereas a quarter of the manholes showed flooding with more complex multipoint methods. Results underline the presence of high uncertainty in design flow estimates. Multipoint hyetograph methods should be used for designing critical infrastructure to minimise flooding risk if no local or regional data are available.